The impact of pregnancy on a woman's health - stress urinary incontinence - Fortuna, Aleksandra; Lipka, Marta; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2020)
Introduction: Urinary incontinence is an embarrassing problem that affects more and more women. The most common type of incontinene in women is stress urinary incontinence, which is defined as the involuntary loss of urine caused by an abnormal closure of the urethra. It happens most often during exercise, coughing or sneezing. The problem of urinary incontinence is extremely important due to the accompanying impact on the psyche of women. It causes a disturbance of self-esteem and is often a cause of embarrassment before visiting a doctor. Results: The pathogenesis of urine loss is multifactorial, but in recent times a lot of blame has been placed on the changes taking place in the body during pregnancy and childbirth. Childbirth weakens the pelvic floor muscles, causing temporary or permanent urine loss. The diagnosis of urinary incontinence is based on the basis of a carefully collected medical history, physical examination and additional tests. Conclusion: Physiotherapeutic procedures, pharmacological treatment and surgical treatment are used as a therapeutic procedures. Prophylactic pelvic floor muscle exercises also play an important role. The most popular treatment for stress urinary incontinence is physiotherapy, including Kegel exercises. The awareness of women about the problem of urinary incontinence should be increased to prevent them from limiting their daily activities and deteriorating sexual activity.